A study on clinico-epidemiological profile of typhoid fever in a rural based medical college & hospital; West Bengal; India - Dr Sudipta Bandyopadhyay; Dr Abhay Charan Pal; Dr Subhendu Dey; Dr Subhendu Samanta; Dr Snehansu Chakraborti; Dr Ramkrishna Mandal (Pediatric Review: International Journal of Pediatric Research, 2017)
Introduction: Typhoid fever is estimated to have caused 26.9 million cases and 5.74 lakhs deaths worldwide in 2010. It remains a major public health problem in India and other part of developing world. Background: Non- provision of safe drinking water and sanitation measures, non-implementation of adequate vaccination strategies and emergence of multidrug resistant salmonella strains is responsible for why typhoid fever is till now remaining an important health problem in some parts of world and the disease is even becoming more complex. Objective: This study was conducted in a tertiary care centre to find out the clinico-epidemiological profile of patients admitted with typhoid fever. Design: Cross sectional observational study. S ubjects: 460 Widal positive typhoid fever pediatric cases admitted from 1st June 2016 to 30th November 2016. Methods: Both clinical and laboratory data of all the patients were retrieved, compiled and analyzed. Results: Out of 460 patients 238(51.74%) were males and 222(48.26%) were females. Fever (100%), vomiting (49.13%), diarrhea (30.21%), cough (30.0%) and hepatomegaly (73.26%) were commonly observed. Response to injection Ceftriaxone was excellent. 355(77.17%) patients responded to Ceftriaxone alone and 99(21.52%) patients needed addition of oral Azithromycin.Average hospital stays in our study ranged from 3-9 days. Conclusion: In the present series typhoid fever accounted for 10.94% of pediatric admissions. Though mortality has significantly reduced typhoid fever continues to be an important cause of hospitalization in pediatric population. High incidence among lower age group indicates high endemicity and emphasizes the need of widespread use of vaccination.